PERAN MAJELIS PEMBINA DAN PENGAWAS PEJABAT PEMBUAT AKTA TANAH DAERAH KABUPATEN KLATEN TERHADAP PENINGKATAN KEPATUHAN PEJABAT PEMBUAT AKTA TANAH DALAM MENJALANKAN TUGAS JABATAN : PERAN MAJELIS PEMBINA DAN PENGAWAS PEJABAT PEMBUAT AKTA TANAH DAERAH KABUPATEN KLATEN TERHADAP PENINGKATAN KEPATUHAN PEJABAT PEMBUAT AKTA TANAH DALAM MENJALANKAN TUGAS JABATAN - Laela Dwi Cahyanni; Supriyadi (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
This study aims to determine and analyze efforts of the Council of Trustees and Supervisors (MPPD) of the Klaten Regency Land Deed Making Official (PPAT) towards increasing PPAT compliance in carrying out the duties of the position. The type of research used is empirical legal research. This study uses secondary data obtained from library materials and primary data obtained form of interviews with respondents and resource persons. The data will then be analyzed qualitatively, then concluded deductively. This research has three conclusions. The role of the MPPD of the Klaten towards increasing PPAT compliance in carrying out the duties of the position is conduct coaching at IPPAT organizational meetings, share the latest info regarding PPAT through WA Group, conduct guidance in the form of inspections to the PPAT office in the context of periodic supervision. Keywords: Regional Trustees and Supervisory Council, PPAT, Compliance, Position Duties, Code of Ethics